Gold price volatility, stock market, and inflation in Turkey: An ARDL approach - Tiryaki, Havva Nesrin (The Economics and Finance Letters, 2025)
This study aims to examine how anticipated gold price volatility affects Turkey’s stock prices and inflation through two distinct models that use Turkey’s country-specific economic uncertainty, industrial output index, and interest rate as control variables. For this purpose, the study first employs the GARCH technique to forecast a conditional variance series, which reveals the volatility of the gold price to reflect the underlying uncertainty and instability within financial markets. Second, by employing this new series, the ARDL approach is used to test the effect of gold price volatility on BIST100 and inflation in Turkey. According to the ARDL results, all variables in Model 1 have significant short- and long-term coefficients. All variables except inflation harm the BIST100 index over time. Additionally, the results suggest that volatility and uncertainty increase inflation in Model 2, while lagged interest rates have a significant impact on inflation, indicating that both internal and external shocks impact inflation and stock prices. These results underscore the transmission of both internal and external shocks to the financial system and pricing dynamics. The findings of the paper emphasize that, in an emerging economy like Turkey, marked by structural weaknesses and heightened susceptibility to global uncertainty, gold price volatility is not only a financial occurrence but a vital factor influencing macroeconomic stability and policy efficacy. Furthermore, external shocks highlight the limited effectiveness of monetary interventions in achieving disinflation objectives.